Pengaruh Peran Kepemimpinan Komunikasi Interpersonal dan Motivasi Kerja Terhadap Kinerja Tutor dalam Memberantas Buta Aksara di Kabupaten Karawang - Banuara Nadeak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Indonesian government is accelerating the National Movement for Accelerating the Nine-Year Compulsory Education Completion and Eradication of Illiteracy. In West Java Province, the illiterate population amounts to 1,512,899 (2.4%), with Karawang Regency having 117,710 illiterate individuals. Karawang has developed a model for eradicating illiteracy within 32 days, starting from preparation, through the process, to implementation of learning activities tailored to the location. Typically, illiterate learners are adults. Effective leadership plays a crucial role in an educative and persuasive approach, enabling smooth interpersonal communication through the use of Knowledge, Information, and Education (KIE) communication techniques. Local governments strive to boost the motivation of tutor teams, supervisors, and monitoring teams in the 32-day illiteracy eradication program. Simultaneously, local governments conduct widespread illiteracy learning activities and have received recognition from MURI (Indonesian World Records Museum) for achieving literacy in reading, writing, and arithmetic. Interpersonal communication enhances the motivation of tutors and relationships with illiterate learners, as evidenced by the evaluation of the success of the 32-day illiteracy learning program. Learners are able to read, write, and calculate (CALISTUNG), and subsequently, they can prepare for equivalency exams (Package A). The outstanding performance of tutors and supervision teams, prepared by the local government of Karawang Regency through the Department of Education and Sports, demonstrates spectacular success. Karawang Regency serves as a model for the 32-day illiteracy eradication program in each province and at the national level.